Challenges in Numeracy: The Role of Mathematics Anxiety in Shaping Eleventh-Grade Students’ Problem-Solving Abilities - Tiara Citra Maharani Firdaus; Sanusi Sanusi; Swasti Maharani (STAI Hubbulwathan Duri, 2025)
This study investigates the learning barriers experienced by eleventh-grade high school students in solving mathematics problems related to numeracy literacy, with particular attention to their levels of mathematics anxiety. Numeracy literacy is essential for students to apply mathematical concepts in real-life contexts; however, many struggle due to cognitive and emotional challenges. Using a qualitative research design, data were collected through classroom observations, semi-structured interviews, and analysis of student work. Participants were selected purposively from a public high school, ensuring variation in performance and reported anxiety levels. The findings reveal that students commonly face difficulties in understanding foundational mathematical concepts, such as fractions, algebraic operations, and data interpretation from tables or graphs. Many also demonstrate limited ability to connect mathematical problems with real-world applications, such as calculating percentages in discounts or interpreting statistical information. Moreover, students struggle to identify relevant information and apply appropriate problem-solving strategies. These barriers are strongly linked to mathematics anxiety, which is evident through behaviors such as hesitation, avoidance, and reduced confidence during numeracy tasks. High-anxiety students often experience deeper conceptual misunderstandings and exhibit less persistence in solving problems. The results suggest that effective instructional approaches should not only address conceptual gaps but also incorporate emotional support to reduce anxiety and improve engagement. Future research is recommended to develop and test targeted interventions aimed at overcoming both cognitive and affective barriers in mathematics learning.